Changes in the human resources market as a key factor of political decisions - G. N. Ryazanova (Управление)
The human resources market is a derivative of the key market for goods and services, the growth of which ensures economic growth in the country. However, it is efficient human resources that enable rational use of natural potential, ensure capital reproduction and new technologies creation. Changes in the labor market can fundamentally transform socio-economic ecosystem and affect the level of political stability in the country. For example, in the 2010s, imbalance in the United Kingdom human resources market provoked political instability that forced the government to withdraw from the European Union. The purpose of the research is to identify impact of the labor market on political decisions on the example of the United Kingdom, to determine causes of disequilibrium in the human resources market, to highlight stages of the European Union and stages of Great Britain’s exit from it, and to present the results of Brexit at the level of the economy and the labor market. The article relies on historical-logical and comparative methods of research, comparison of macroeconomic indicators dynamics on the basis of a systematic approach. Statistical data of the World Bank and the Office for National Statistics allow us to confirm mutual influence of the labor market and the policy of the country’s government.